2016
DOI: 10.1016/j.amj.2016.08.003
|View full text |Cite
|
Sign up to set email alerts
|

Reporting Helicopter Emergency Medical Services in Major Incidents: A Delphi Study

Abstract: Objective: Research on helicopter emergency medical services (HEMS) in major incidents is predominately based on case descriptions reported in a heterogeneous fashion. Uniform data reported with a consensus-based template could facilitate the collection, analysis, and exchange of experiences. This type of database presently exists for major incident reporting at www.majorincidentreporting.net. This study aimed to develop a HEMS-specific major incident template. Methods: This Delphi study included 17 prehospita… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…A recent systematic review indicated a need for more knowledge on the role of Helicopter Emergency Medical Services (HEMS) in major incidents [ 15 ]. This lead to a consensus process being undertaken to create a HEMS major incident reporting template [ 16 ]. This template is also now available on majorincidentreporting.net.…”
Section: Introductionmentioning
confidence: 99%
“…A recent systematic review indicated a need for more knowledge on the role of Helicopter Emergency Medical Services (HEMS) in major incidents [ 15 ]. This lead to a consensus process being undertaken to create a HEMS major incident reporting template [ 16 ]. This template is also now available on majorincidentreporting.net.…”
Section: Introductionmentioning
confidence: 99%
“…HEMS is a limited and expensive resource that requires very skilled and trained personnel [ 15 ], so doing an entire scientific evaluation of its use and its potential benefits is so important and essential in incident management. The most important component of preparedness during incidents is to hold maneuvers and exercises [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
“…HEMS is a limited and costly system that needs skilled and trained staff. So, doing an entire scientific evaluation is essential to its use and its potential benefits [ 17 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This compromises the opportunity to learn from such events and develop systems that could improve the response to future Major Incidents. Several Major Incident reporting templates have been published [ 18 ] and one online template has been developed to specifically assess the pre hospital response [ 2 , 19 ].…”
Section: Ehac Mwg Statementmentioning
confidence: 99%